Expression and Roles of Lynx1, a Modulator of Cholinergic Transmission, in Skeletal Muscles and Neuromuscular Junctions in Mice - Doss, Sydney V.; Barbat-Artigas, Sébastien; Lopes, Mikayla; Pradhan, Bhola Shankar; Prószyński, Tomasz J.; Robitaille, Richard; Valdez, Gregorio (Frontiers in Cell and Developmental Biology, 2022)
Lynx1 is a GPI-linked protein shown to affect synaptic plasticity through modulation of nicotinic acetylcholine receptor (nAChR) subtypes in the brain. Because of this function and structural similarity to α-bungarotoxin, which binds muscle-specific nAChRs with high affinity, Lynx1 is a promising candidate for modulating nAChRs in skeletal muscles. However, little is known about the expression and roles of Lynx1 in skeletal muscles and neuromuscular junctions (NMJs). Here, we show that Lynx1 is expressed in skeletal muscles, increases during development, and concentrates at NMJs. We also demonstrate that Lynx1 interacts with muscle-specific nAChR subunits. Additionally, we present data indicating that Lynx1 deletion alters the response of skeletal muscles to cholinergic transmission and their contractile properties. Based on these findings, we asked if Lynx1 deletion affects developing and adult NMJs. Loss of Lynx1 had no effect on NMJs at postnatal day 9 (P9) and moderately increased their size at P21. Thus, Lynx1 plays a minor role in the structural development of NMJs. In 7- and 12-month-old mice lacking Lynx1, there is a marked increase in the incidence of NMJs with age- and disease-associated morphological alterations. The loss of Lynx1 also reduced the size of adult muscle fibers. Despite these effects, Lynx1 deletion did not alter the rate of NMJ reinnervation and stability following motor axon injury. These findings suggest that Lynx1 is not required during fast remodeling of the NMJ, as is the case during reformation following crushing of motor axons and development. Instead, these data indicate that the primary role of Lynx1 may be to maintain the structure and function of adult and aging NMJs.